Demonophobia pada Tokoh Kusano Tetsuya dalam Novel Bonus Track Karya Koshigaya Osamu - Ema Rindayani, Putu; Ari Sulatri, Ni Luh Putu; Wiriani, Ni Made (Humanis; Vol 23 No 4 (2019), 2019)
This research is titled "Demonophobia in Kusano Tetsuya's character in Bonus Track’novel by Koshigaya Osamu". This study aims to determine the symptoms and ways to overcome demonophobia in Kusano Tetsuya’s character. The method used descriptive analysis method. The theory used literary psychology that proposed by Ratna (2006) and the theory of specific phobia proposed by Hogan (2004). The analysis of fear or anxiety that occurs to Kusano can cause adverse effects on daily life. Based on the results of the analysis it can be concluded that someone who experiences demonophobia has problems that can be cured with symptoms that suffer. Changing mindset is an influential step for Kusano Tetsuya in an effort to overcome the demonophobia because at that step makes Kusano slowly to recover from his phobia.